Mapping risks in UNILA acquisitions - Sturmer, Robinson Alexander; Dechechi , Eduardo Cesar; Garcia , Elias (Seven Editora, 2023)
Public acquisitions of goods and services provide the demands for the fulfillment of the functions of the State. It happens that the routine of public institutions is permanently exposed to risks and uncertainties, and in this context, risk management can promote the improvement of the quality of public spending. The problems that occurred during the purchase represent the materialization of the risks and make explicit the need for the adoption of tools to mitigate its consequences. The study of these processes, considering the relevant information from the contractual execution phase of the acquisitions and their mapping, can provide subsidies to answer the following question: What risks permeate the execution of public contracts for the acquisition of goods and materials within the scope of the Federal University of Latin American Integration (UNILA)? To meet the proposed objective, descriptive research was used, having the case study as a strategy. The analysis of these processes allowed us to identify which risks permeate the execution of public contracts for the acquisition of goods and materials within the scope of UNILA and thus propose tools for mitigation and control, based on the use of the methodology proposed by PMBOOK. DOI:https://doi.org/10.56238/alookdevelopv1-059